A Study of The Biological Effect of Egy Pride on The Quantitative Genetic Variation of The Cucurbit Fruit Fly, Dacus Ciliatus (Diptera: Tephritidae) - Shatha, A. Mahdi; Hussein, M. Prism; Ashwak, T. Humadi (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the influence of the insecticide Egy Pride on the quantitative genetic variation and wing morphology of the Cucurbita fruit fly, Dacus ciliatus, a pest of agricultural significance. Geometric morphometrics were applied to analyze the shape and size of right wings from 30 specimens, half of which were treated with Egy Pride. The analysis revealed a 67% match rate in landmark coordinates between treated and untreated specimens, with notable deviations at landmarks 2, 6, 8, 9, and 15. Treated specimens exhibited variations in wing shape and size, with a central size measurement of 868.6 microns compared to 850.8 microns in the control group. Statistical analysis showed a Mahalanobis distance of 9.49, indicating differentiation between the groups. Classification rates based on wing morphology were 74% for treated and 53% for untreated specimens, with an 83% rate when based on the Mahalanobis distance. The study suggests that Egy Pride induces quantitative genetic variation and morphological changes in D. ciliatus, potentially affecting their flight and mobility. These findings highlight the unique properties of Egy Pride in pest control and its impact on the genetic and morphological aspects of targeted species.